The variable effect of form and lemma frequencies on phonetic variation: evidence from /s/ realization in two varieties of Colombian Spanish - Brown, Earl K.; Gradoville, Michael S.; File-Muriel, Richard J. (My University, 2015)
Research has shown that frequency conditions the variable realization of sounds. However, the literature has not addressed whether the frequency of the individual word forms, or form frequency, has a larger conditioning effect than the combined frequencies of the members of the paradigm to which the forms belong, or lemma frequency. Monofactorial correlation tests and monofactorial and multifactorial linear regression analyses are performed on 2,734 tokens of Spanish /s/ in sociolinguistic interviews conducted in Cali and Barranquilla, Colombia. Two findings are highlighted: (1) frequency is only significant in the variety of Spanish that has low overall rates of /s/ reduction, Cali, and (2) form frequency is more influential than lemma frequency.
Keywords: Frequency effects; Form frequency; Lemma frequency; Spanish /s/; Colombian Spanish; Activation state